COACH-ATHLETE RELATIONSHIP IN BRAZILIAN MEN'S ARTISTIC GYMNASTICS - Pauline Iglesias Vargas; Mauricio Santos Oliveira; André Mendes Capraro (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
This research aimed to indicate, from the standpoint of athletes of the Brazilian men's artistic gymnastics national team between 2013 and 2021, characteristics of the relationship with their coaches. Five such Brazilian athletes were interviewed, employing thematic analysis. It was identified that the coaches' current behaviour is ethical, although athletes did not deny a recent history of abusive patterns. The exchange of knowledge with foreign coaches and the work of sports regulating bodies proved positive to bring about changes in the said relationship. Athletes reported mutually respectful relationships with their coaches and were sorry for the little value given to the profession in the country.